Level of and associated factors for non-adherence to anti-tuberculosis treatment among tuberculosis patients in Gamo Gofa zone, southern Ethiopia: cross-sectional study - Dessalegn Ajema; Tamiru Shibru; Temesgen Endalew; Selamawit Gebeyehu (BMC, 2020)
Abstract Background Non-adherence to anti-TB treatment is one of the crucial challenges in improving tuberculosis (TB) treatment outcomes and reducing healthcare costs. The poor adherence to anti-TB treatment among patients with TB is a major problem in Ethiopia. This study aimed to assess the level of and associated factors for non-adherence to anti-TB therapy among patients with tuberculosis in the Gamo Gofa Zone. Methods A cross-sectional study was conducted at Gamo Gofa Zone from July 20 - August 30, 2017. A multi-stage sampling technique was used. The study included 289 patients who were on anti-TB treatment. Data were collected by trained data collectors using a structured and pre-tested questionnaire through interviews. A multiple logistic regression model was fitted using SPSS 23 to identify factors associated with non-adherence to anti-TB treatment at a 5% significance level. Results We found that 16.5% of the participants were non-adherent for anti-TB treatment. Failure to disclose one's TB status to his or her family (AOR = 31.7; 95% CI: 9.1-111.1), having no information on the expected adverse events (AOR = 31.1; 95% CI: 7.5-128.3), past anti-TB treatment history (AOR = 5.3; 95% CI: 1.5-18.8) and a smoking cigarette (AOR = 11.7; 95% CI: 3.2-43.03) were found to be associated with a higher odds of being non-adherent to anti-TB treatment. Conclusions The level of non-adherence to anti-TB treatment among TB patients was high. Health care providers should counsel TB patients on the expected adverse events and measures to be taken when patients face the expected adverse events. They should also counsel their patients to disclose their TB status to his or her family and for ceasing cigarette smoking.